1967
DOI: 10.1039/tf9676302549
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of chloromethyl silanes with hydrated Aerosil silicas

Abstract: Methyl chlorosilane vapours react with the surface hydroxyls of Aerosil silicas at temperatures above about 250°C. Infra-red spectroscopic studies on deuterium exchanged samples show that only the external hydroxyl-groups are affected. The trimethyl-and dimethyl-substituted chlorosilmes react selectively but completely with the isolated or single surface hydroxyls, whereas the monomethyl and tetrachloro compounds also react with some of the interacting hydrogen-bonded surface groups. Analyses of the solid reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…Therefore it is not surprising that first attempts to passivate surface silanol groups were undertaken with respect to these composites [65]. Methyltrichloro-(MTCS [66,67]), dimethyldichloro-(DMDCS [66][67][68]) or trimethylchlorosilanes (TMCS [67][68][69]) were applied for gas phase functionalization from room temperature to 300 [66] or 400 • C [67]. The presence of NH 3 catalyzed the reaction and resulted in a high surface coverage of organosilanes at relatively lower reaction temperatures than without catalyst [69].…”
Section: Sio 2 Nanoparticlesmentioning
confidence: 99%
“…Therefore it is not surprising that first attempts to passivate surface silanol groups were undertaken with respect to these composites [65]. Methyltrichloro-(MTCS [66,67]), dimethyldichloro-(DMDCS [66][67][68]) or trimethylchlorosilanes (TMCS [67][68][69]) were applied for gas phase functionalization from room temperature to 300 [66] or 400 • C [67]. The presence of NH 3 catalyzed the reaction and resulted in a high surface coverage of organosilanes at relatively lower reaction temperatures than without catalyst [69].…”
Section: Sio 2 Nanoparticlesmentioning
confidence: 99%
“…Organic molecules can also interact with silica, but depending on the form of interaction they either prevent dissolution of silica or induce it by forming a soluble complex. Reaction of silica with trimethylchlorosilane results in a chemisorbed surface layer of alkyltrimethylsilane, which make silica particles hydrophobic and prevent their dissolution . On the other hand, o‐dihydroxy arylenes, as for example catechol, form soluble complexes with silicon which are stabile in aqueous solutions, but however not stabile toward atmospheric pressure …”
Section: Silica Chemistrymentioning
confidence: 99%
“…Reaction of silica with trimethylchlorosilane results in a chemisorbed surface layer of alkyltrimethylsilane, which make silica particles hydrophobic and prevent their dissolution. 2,41 On the other hand, o-dihydroxy arylenes, as for example catechol, form soluble complexes with silicon which are stabile in aqueous solutions, but however not stabile toward atmospheric pressure. 2,42 In aqueous solutions at pH 8 and room temperature, amorphous silica and to some extent quartz were solubilized by various o-dihydroxy arylenes.…”
Section: Solubility Of Silicamentioning
confidence: 99%
“…De Boer and Vleeskens [16] argue that the silica loses this adsorbed water at around 120 o C in ambient air, unless it is present in micropores, where the loss is at 180 o C. Drying under a vacuum, at low temperature is also an effective technique to remove all the surface adsorbed water. Armistead and Hockey [17] found that removal of the silanol group takes place around 400-450 o C in ambient air where half of the hydroxyl groups leave the silica surface creating large siloxane areas that do not rehydrate readily.…”
Section: Silica Structurementioning
confidence: 99%